Framework of National Cancer Control Program in Indonesia - Aditama, Tjandra Yoga (Indonesian Journal of Cancer, 2008)
Framework of National Cancer Control Program in IndonesiaÂ full text: http://www.scribd.com/doc/45152743/Framework-of-National-Cancer-Control-Program-in-Indonesia